Morphogenesis, Programmed Cell Death and Antibiotic Formation in Streptomycetes Under Conditions of Submerged Growth - K. A. Vinogradova; S. N. Filipova; A. N. Polin (Антибиотики и Химиотерапия)
Members of the genus Streptomyces are mycelial bacteria that undergo a complex life cycle that makes them similar to multicellular organisms. Streptomycetes are important industrial microorganisms, as they produce a plethora of medically relevant natural products, including the majority of clinically important antibiotics. This review addresses the morphogenesis of streptomycetes in submerged growth conditions in connection with the biosynthesis of antibiotics, as well as the events of programmed cell death in the course of the producer's development.